Evolution of New Working Spaces Changing Nature and Geographies - Mariotti, Ilaria; Tomaz, Elisabete; Micek, Grzegorz; Méndez-Ortega, Carles (PoliMI SpringerBriefs,, 2024)
This open access book provides multidisciplinary perspectives on the changing dynamics of new working spaces, with insights from various European countries and observing critical theoretical approaches. Divided into two main parts, the first part focuses on the different typologies of new working spaces, identifying the changing nature of these spaces and associated concepts, taxonomies, and specific approaches to this phenomenon. The second part analyzes the location of new working spaces, examining its recent evolution and identifying new factors and geographies, offering an additional empirical analysis of different European realities. The research included in this book contributes to the current discussion of new forms and geographies of work and their impact on the territories and related policies.